Evaluasi dan Analisis Stabilitas Lereng Pasca Longsor Datarajan, 24 Mei: Studi Geoteknik dan Penanganan Segera - Syah, Aminudin; Alami, Fikri (Faculty Of Engineering University 17 August 1945 Semarang, 2025)
A landslide that occurred on May 24, 2024, in Pekon Datarajan, Ulubelu District, Tanggamus, Lampung, caused significant disruption to provincial road access and resulted in material losses. This study aims to assess the post-failure slope stability through field geotechnical investigation and numerical analysis using the Limit Equilibrium Method (LEM), and to propose immediate countermeasures. The slope materials consist of MH (inorganic silt) and ML (elastic silt) with high moisture content and moderate to high swelling potential. The lithology is dominated by montmorillonite clay, which has hygroscopic characteristics, making it highly vulnerable to water infiltration that reduces shear strength and increases the risk of slope failure. Stability analysis indicates a post-failure factor of safety (FoS) of 1.36 (static loading) and 1.03 (dynamic loading), which decreases to 1.07 beneath raised groundwater conditions. Recommended immediate mitigation includes surface runoff control, the construction of impermeable drainage systems, the sealing of cracks using impermeable materials, and the installation of temporary slope reinforcements such as sheet piles. The implementation of these measures increased the FoS to 1.61 (static loading) and 1.16 (dynamic loading). This study provides a technical basis for the rapid and effective mitigation of landslides in areas with similar geological and hydrological conditions.